Menilai Dampak Penyaluran Likuiditas Pemerintah Tahun 2025 terhadap Stabilitas dan Keadilan Ekonomi:Perspektif Maqāṣid al-Syarī‘ah - Nurida Isnaeni; Amaludin Efendi Harahap; Dela Fauzia; Rama Fajri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study evaluates the effectiveness of Indonesia’s 2025 liquidity injection of IDR 200 trillion into state-owned banks (Himbara) through the lens of Islamic economics and maqāṣid al-syarī‘ah. Using a qualitative–descriptive method based on library research, the study examines whether the policy has succeeded in promoting productive financial intermediation, economic stability, and just liquidity distribution. Data were drawn from Bank Indonesia, the Ministry of Finance, the Financial Services Authority (OJK), and peer-reviewed publications indexed in SINTA and Scopus.Findings reveal that as of October 2025, 84% of the injected funds had been disbursed, but only 18–22% were channeled to SMEs, far below the 37% allocation during the 2020 PEN stimulus. Moreover, 30–40% of the liquidity was placed in money market instruments and government securities rather than real-sector financing. Credit growth slowed from 7.7% (September) to 7.36% (October 2025), indicating weak transmission and raising concerns about moral hazard when liquidity strengthens bank reserves without productive allocation. Thus, integrating the liquidity program with productive financing schemes, Islamic financial inclusion, and robust Sharia governance is essential to align the policy with maqāṣid al-syarī‘ah.